STUDI PERILAKU HARIAN MONYET EKOR PANJANG ( Macaca fascicularis ) DI PULAU TINJIL - Suwarno Suwarno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Long-tailed monkeys (Macaca fascicularis) has wide area deployment. They are social animals that interact each other. The purpose of this study was to determine the long-tailed monkey daily activities (Macaca fascicularis) that live around the base camp on the Tinjil Island  Banten . The method used for observation of daily activities using scan sampling. Most done activity from this research is foraging. The percentage of daily activity are  fo: 43.45% foraging; move 22.96%; silent 12.59%; Grooming 10%; playing 5.92%; agonistic 3.70%; sleep 1.38%. Keywords: Macaca fascicularis, long-tailed monkeys, behavior, scan sampling